Seasonality of birth patterns in an Australian cohort of patients with biopsy‐confirmed idiopathic inflammatory myopathy. Issue 5 (May 2016) - Woodman, R.; Hakendorf, P.; Limaye, V.
Abstract : Environmental exposures in the foetal period may predispose to autoimmunity. Aim of this study is to investigate whether seasonality in birth patterns exists in idiopathic inflammatory myopathies (IIM). We used Stata (StataCorp USA, version 13.0) and the user‐written routine command 'circsummarise' to assess birth seasonality among South Australian patients with histologically confirmed IIM subsequent to 1980 using their date of birth. There was no evidence for a seasonal birth pattern among IIM patients overall ( n = 568), however there were some ethnic variances in birth patterns among non‐Caucasian patients. There was evidence for birth seasonality among both Aboriginal (mean = 7 July, Rayleigh P = 0.04) and Asian patients (mean = 12 August, Rayleigh P ‐value = 0.038). Non‐Caucasians born in the third quarter of the calendar year may have an increased risk of developing IIM. Large international studies of IIM patients of diverse ethnicity are required to clarify the role of perinatal exposures in disease susceptibility.